The Tyranny of the Epochal: Change, Epochalism and Organizational Reform - du Gay, Paul (Organization (London, England), 2003)
The paper focuses upon a particular discourse of organizational ‘change’ as it has appeared in a specific context—the contemporary field of public administration—and seeks to explore its role as a rhetorical device in reshaping the identity of public service. It does so first by seeking to indicate the epochalist bent of much theorizing about contemporary economic and organizational change—in both its academic and its more managerial manifestations. Second, it seeks to show how a particular discourse of organizational change mobilizes support for attempts to ‘re-invent’ or ‘modernize’ the public administration as an institution of government. Finally, it seeks to offer a few words in support of the seemingly unfashionable art of ‘piecemeal reform’ or ‘ organizational casuistry’.